2017
DOI: 10.3899/jrheum.161529
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Rheumatologists: Use and Benefits of an Electronic Consultation Service

Abstract: There are clinical questions that can be answered quickly by an eConsult, improving access to rheumatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 9 publications
5
41
1
2
Order By: Relevance
“…Incorporating anti-DFS70 antibodies into the evaluation of positive ANA Econsults could be a potential way to avoid unnecessary testing [19] and give reassurance that a patient will not likely develop an AARD over time [20]. The average rheumatology response time to E-consult in our study was similar to prior studies using asynchronous telehealth modalities [2,10].…”
Section: Resultssupporting
confidence: 75%
“…Incorporating anti-DFS70 antibodies into the evaluation of positive ANA Econsults could be a potential way to avoid unnecessary testing [19] and give reassurance that a patient will not likely develop an AARD over time [20]. The average rheumatology response time to E-consult in our study was similar to prior studies using asynchronous telehealth modalities [2,10].…”
Section: Resultssupporting
confidence: 75%
“…Sleep medicine e-consultation followed by the specialists' order of a sleep study and positive airway pressure therapy, if indicated, resulted in a decrease over 4 years in the interval between sleep consult and positive airway pressure prescription from 60 days to 7 days. 38 More than a dozen studies report a response time (i.e., the time between when the e-consult is requested and when the responding specialist provides the response) of a few days or less, 11,13,14,16,20,21,28,32,34,35,40,46,47,51,56,61,62,67,69 whereas face-toface visits generally require days to weeks to be completed.…”
Section: Access To Carementioning
confidence: 99%
“…62 Several publications from the Champlain BASE program report on a PCP survey question at the end of each e-consult request about whether a face-to-face consult would have been sent in the absence of the e-consult option. Depending on specialty of the consultation being requested, 32%-80% of PCPs report that a face-to-face visit would have been required absent the e-consult, [12][13][14]16,[18][19][20][21]24,26,[28][29][30][31][32][33][34][35][36]41,47,51,58,62,65 suggesting that up to as many as 4 out of 5 e-consults are perceived to obviate a face-to-face visit. Using these data on face-to-face referrals avoided, the Champlain BASE group calculated payer costs decreasing from $131.05 to $6.45 (CAD) per econsult from year 1 to year 3 of the program.…”
Section: Costsmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, there has been a rapid increase in telehealth usage in 2020 [1]. One type of telehealth format, the electronic consult (E-consult), has been utilized by healthcare systems in the United States and internationally for many years [2,3] as a way to help patients gain access to specialty care. E-consults are an asynchronous form of communication between referring provider and specialist through a shared EHR (electronic health record) or web-based platform that entails the specialist reviewing chart data and replying with recommendations electronically [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…One study evaluated E-consults in rheumatology and showed advantages including quicker turn-around times, a decrease in face-to-face visits, and increased referring provider satisfaction. Common reasons E-consults were utilized in this study included treatment questions, questions about whether a patient required an in-person evaluation, and interpretation of a positive laboratory test [2].…”
Section: Introductionmentioning
confidence: 99%